(untitled) (Journal of Pakistan Orthopaedic Association, 2019)
Objective: To determine patterns of trauma in paediatric population presenting to Orthopaedic Department in a tertiary care hospital of Swat. Methods: This retrospective study was conducted in department of orthopaedics and traumatology, Saidu Group of Teaching Hospitals, Swat from January, 2017 to December, 2017. The medical records of all patients (0-14 years) with trauma admitted in our unit were analysed retrospectively. Demographic details of the included subjects were noted down. Results: A total of 675 patients were included in our study; 478 males and 197 females. Patients with 6-10 years were 49%, 0-5 years were 26% and 11-14 years, 25%. Supra condylar humerus fracture (26.8%) preceded shaft of femur fracture (23%), followed by radius, ulna fracture (14%), then other injuries like small bone fractures, soft tissue injuries and foreign bodies. Only 2 cases of pelvic and pathological fractures each were noted. Fall injuries surpassed road traffic accidents. Conclusion: Male boys below ten years were common. History of fall resulting in supracondylar fractures were the commonest mode of injury sustained